Method of determining priorities in the quantitative estimation of risk factors in the work of flight dispatchers - Бєляєвський, Л. С.; Біндас, О. Б. (Proceedings of National Aviation University (archive), 1999)
Considered are the risk factors, which can produce negative effect on flight dispatchers in the process of direct air traffic control. The achieved results can be used for estimation of potential danger of flight dispatchers